TEACHER PROFESSIONAL COMPETENCE IN APPLYING THE PROBLEM MODEL BESED LEARNING IN CLASS IV INTEGRATED THEMATIC LEARNING SDN 2 TOMBULANG - SARLIN PATILIMA; ABDUL RAHMAT; MOHAMAD ZUBAIDI; RUSMIN HUSAIN (International Journal of Innovations in Engineering Research and Technology, 2021)
Professional competence is the ability of a teacher to manage the teaching and learning process. The ability to manage learning supported by classroom management, mastery of learning materials, teaching strategies and use of learning media must be owned by a professional teacher. The Problem Based Learning (PBL) model is a learning model that challenges students to learn by working together in groups, meaning that the teacher needs to explain the learning objectives and activities to be carried out so that students know what the main objectives of learning are, as well as the problems to be discussed. This learning model is used by grade IV teachers at SDN 2 Tombulang in providing integrated thematic lessons in Theme 4 in their class IV. With this competence, this teacher can produce changes in student learning in integrated thematic learning in learning theme 4.